An assessment of Ultrasound screening for soft tissue lumps referred from primary care. Issue 12 (December 2018) - Charnock, M.; Kotnis, N.; Fernando, M.; Wilkinson, V.
Abstract : Aims: To assess the efficacy of ultrasound as a screening tool in the assessment of soft-tissue masses referred from primary care and to investigate the incidence of malignancy in this population. Materials and methods: Retrospective analysis was performed on patients who underwent ultrasound for a suspected soft-tissue mass at our centre between January 2011 and December 2012. Patient demographics, ultrasound findings, further imaging investigations and histopathology were recorded. Patient records were followed up for a minimum period of 4 years. Results: A benign sonographic diagnosis was found in 95% (2271/2399) patients and 91% (2069/2399) required no further imaging or histopathology assessment. Ninety-six patients with a benign sonographic diagnosis had a benign histological diagnosis and one patient was found to have a histologically proven malignancy. Five percent (122/2, 399) had an indeterminate scan. Of these, 40 had a histologically proven benign lesion and 10 had a histologically proven malignancy. Six of the 2, 399 (0.2%) patients had scans suggestive of malignancy with histological confirmation. In total, 0.7% (17/2399) had proven malignant lesions. Eight were sarcomas. Conclusion: The present study, which to the authors' knowledge is the first to focus on ultrasound assessment of musculoskeletal masses referred solely from primary care, confirms ultrasound as a highly effective screening tool. It often avoids the need for further investigation and inappropriate clinical referrals. Malignant lesions are very rare in this patient cohort. Highlights: Vast majority of soft tissue masses seen in primary care are benign. Ultrasound has a high sensitivity, specificity and accuracy compared to histology. Supports Ultrasound as a screening tool for imaging of primary referral soft tissue masses.